Fall-related sub-acute and non-acute care and rehabilitation-related acute care: what is the impact?. (7th October 2012) - Mitchell, R; Close, J; Cameron, ID; Lord, S
Abstract : Background: Falls are one of the leading causes of injury in older people. Rehabilitation services can assist individuals to improve mobility and function after sustaining a fall-related injury. However, the true impact of fall-related injuries resulting in hospitalisation are often underestimated because of failure to consider sub-acute and non-acute care provided following an acute care episode. Aim: To examine fall-related sub-acute and non-acute care and to establish and project the burden of fall-related rehabilitation in acute care to 2020. Method: Retrospective review of sub-acute and non-acute records linked to hospital admission and/or emergency department presentations during 2001–2002 to 2008–2009 in New South Wales (NSW), Australia. Analysis of temporal trends and projections to 2020 of rehabilitation-related (ICD-10-AM: Z47, Z48, Z50, Z75.1) acute hospital admissions. Results: There were 4317 individuals with a fall-related injury who were admitted to hospital and later admitted for sub-acute and non-acute care; 84% of these were aged 65+ years; 70.4% were female; 27.2% had femur fractures. Total mean FIM scores significantly increased from 78.4 to 94.6 (p<0.0001) between admission and discharge. Fall-related acute rehabilitation episodes are increasing by 9.1% each year for individuals aged 65 years and older and are projected to rise from 18 300 in 2010–11 to 50 000 admissions by 2020. Significance: This is the first study to provide a snap-shot of the epidemiological profile of individuals using sub-acute and non-acute care in NSW using linked data. This information can be used to inform resource implications for fall-related sub-acute and non-acute care and acute rehabilitation services.